Cell type census in cerebral cortex reveals species-specific brain function and connectivity - Kohei Onishi; Tomomi Shimogori (Neuroscience Research)
The cerebral cortex contains a diverse array of functional regions that are conserved across species, such as primary somatosensory and primary visual cortex. However, despite this conservation, these regions exhibit different connectivity and functions in various species. It is hypothesized that these differences arise from distinct cell types within the conserved regions. To uncover these species-specific differences, investigating gene expression at the cellular level can reveal unique cell types. In this review, we highlight recent research on the molecular mechanisms that govern the formation of specific cell types in the rodent primary somatosensory cortex. Furthermore, we explore how these conserved molecular mechanisms are observed across different brain regions in various species. These findings offer new insights into the diversity and evolutionary background of neural circuit formation in the mammalian cortex.